Reactive oxygen species production by blood leukocytes and its correction by trimetazidine MB in patients with acute coronary syndrome - M. G. Glezer; S. V. Kulikov; R. T. Saygitov; E. I. Astashkin (Кардиоваскулярная терапия и профилактика)
Aim. In patients with acute coronary syndrome (ACS), to detect pre-activated (primed) phagocytes in peripheral blood and  to evaluate the effects of trimetazidine MB, when added to standard therapy, on reactive oxygen species (ROS) production. Material and methods. In 113 hospitalised ACS patients – 86 with myocardial infraction (MI) and 27 with unstable angina  (UA) – the dynamics of blood leukocytes and ROS (baseline activity and PMA (phorbol-12-myristate-13-acetate) stimulated activity) was assessed by lucigen-dependent chemiluminescence method. In 60 participants, trimetazidine MB (70  mg/d) effects on ROS production were investigated. Results. At hospital admission, blood leukocyte levels, basal and PMA-stimulated ROS production were significantly  higher in AMI patients (especially in those who subsequently died) than in UA participants. Trimetazidine MB therapy  facilitated more rapid and manifested leukocyte count reduction, compared to the standard therapy alone: the respective  reductions at Days 3-5, 7-10, and 15-21 were -20 vs. -14%, -37 vs. -30%, and -47 vs. -32%. In the trimetazidine MB group,  the basal and PMA-stimulated ROS production did not change significantly, while in the standard therapy group, the ROS  production increased from Day 3 to Day 15.Conclusion. Adding trimetazidine MB to standard therapy of ACS patients significantly reduced the peripheral blood leukocyte count at Days 15-21, without leukocyte activation in the sub-acute phase of myocardial ischemia.